2017
DOI: 10.1108/afr-03-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Farm income and output and lending by the farm credit system

Abstract: Purpose The purpose of this paper is to provide evidence of the positive impact of the FCS lending on farm incomes which should be useful to policymakers as they consider reforms and further support for this 100-year-old major agricultural lender. Design/methodology/approach The authors construct a panel for the 1991-2010 period from the FCS financial statements and evaluate how lending by the FCS institutions has affected farm incomes and farm output. The authors use fixed effects estimations and control fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Hasil tersebut telah sesuai dengan penelitian (Nadolnyak et al, 2017) bahwa nilai output berpengaruh postif dengan permintaan kredit. Didukung dengan hasil penelitian Onal, Darmawan, & Jhonson, (2015) yang menyebut bahwa pendapatan pertanian meningkat dengan adanya peningkatan ketersediaan kredit bersubsidi kepada petani kecil.…”
Section: Harga Gabahunclassified
“…Hasil tersebut telah sesuai dengan penelitian (Nadolnyak et al, 2017) bahwa nilai output berpengaruh postif dengan permintaan kredit. Didukung dengan hasil penelitian Onal, Darmawan, & Jhonson, (2015) yang menyebut bahwa pendapatan pertanian meningkat dengan adanya peningkatan ketersediaan kredit bersubsidi kepada petani kecil.…”
Section: Harga Gabahunclassified
“…Although often considered mainly a developing country issue, prior studies have concluded that the U.S. farms also face binding and non-negligible credit constraints (e.g., Briggeman, et al, 2009b;Chaddad et al, 2005;Hartarska and Nadolnyak, 2012;Mishra et al, 2008). Limited credit has been found to adversely impact the U.S. farm income and output (Briggeman, et al, 2009b;Nadolnyak et al, 2017), rural economic growth (Hartarska, et al, 2015), Tennessee small farms' financial performance (Khanal and Omobitan, 2020), amount of farm inputs used (Kumar et al, 2013), Midwest grain yields (Butler and Cornaggia, 2011), and farm efficiency (Chavas and Aliber, 1993). Mugera and Nyambane (2015) observed that the technical efficiency of broadacre farms (large-scale agricultural or pastoral enterprises that produce grains, oilseeds, or other crops or graze livestock for meat or wool) in Western Australia was positively related to short-term debt.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is also segmentation in the rural financial market (Nadolnyak, Shen, and Hartarska, 2017). The major financial institutions-Farm Credit System (FCS) and commercial banks are considered the major lenders for agricultural loans in the United States-tend to serve well-equipped farmers with a high degree of credibility, while farmers with lower incomes with low-collateral ability face significant challenges.…”
Section: Introductionmentioning
confidence: 99%